2003
DOI: 10.1007/bf03218350
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 5-fluorouracil-loaded poly(L-lactide-co-glycolide) wafer and evaluation ofin vitro release behavior

Abstract: The controlled delivery of anticancer agents using biodegradable polymeric implant has been developed to solve the problem of penetration of blood brain barrier and severe systemic toxicity. This study was performed to prepare 5-FU-loaded poly(L-lactide-co-glycolide) (PLGA) wafer fabricated microparticles prepared by two different method and to evaluate their release profile for the application of the treatment of brain tumor. 5-FU-loaded PLGA microparticles were characterized by scanning electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 21 publications
6
11
0
Order By: Relevance
“…Hence, sharp peaks observed in the case of HA-PEG-PLGA-FU nanoparticles reveal that the crystalline nature of 5-FU is retained even when the drug is encapsulated in the nanoparticles. These findings are in line with those reported by Lee et al (2003).…”
Section: X-ray Diffractionsupporting
confidence: 94%
See 1 more Smart Citation
“…Hence, sharp peaks observed in the case of HA-PEG-PLGA-FU nanoparticles reveal that the crystalline nature of 5-FU is retained even when the drug is encapsulated in the nanoparticles. These findings are in line with those reported by Lee et al (2003).…”
Section: X-ray Diffractionsupporting
confidence: 94%
“…Plain 5-FU showed an exothermic peak at 285°C, as already reported . These findings are in line with those reported by Luo et al (2000) and Lee et al (2003).…”
Section: Differential Scanning Calorimetrysupporting
confidence: 93%
“…The extrapolated onset temperature in thermograms denotes the temperature at which the weight loss begins. The extrapolated onset temperature of 5-FU is 286.9 o C. The DSC thermogram of the pure 5-FU also showed a sharp melting endotherm peak at approximately 286.9 °C followed by decomposition, which was in agreement with those reported previously (Lee et al, 2003). The red curve is the % weight loss curve and it indicated that % Weight loss occurs in one step with 90% decomposition of the drug between 280 °C to 350 °C.…”
supporting
confidence: 90%
“…The total amount of drug released was similar for PCL/FU tablets manufactured using the lower and higher laser powers and are associated with small differences presented by both condition in the sintering degree and porosity. This drug release pattern is very common with FU polymeric drug delivery systems and has been reported by many researchers [31][32][33]. The initial amount of FU released by the sintered PCL/FU tablets is a desirable profile to provide a high initial concentration of the drug locally in the cancer cells following implantation.…”
Section: Resultsmentioning
confidence: 63%